The contribution of missionaries to Shona lexicography - Viriri, Advice (Lexikos, 2016)
This article is a revised version of a paper presented at the Seventh International Conference of the African Association for Lexicography, organised by the Dictionary Unit of South African English, Rhodes University, Grahamstown, Republic of South Africa, 8–10 July 2002